OPTIMALISASI KINERJA UMKM PARIWISATA MELALUI PENGUATAN PROMOSI DIGITAL DAN LAYANAN DI ABU TOUR - Amelianda, Amelianda; Wulandari, Ika (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service program was conducted to support Abu Tour & Travel, a small business in the travel service sector, in optimizing its performance through digital transformation. The main issues identified were the suboptimal use of digital platforms for promotion and the inefficiency of the existing customer service system. The program aimed to enhance digital marketing capabilities and improve customer service to strengthen competitiveness in the digital era. The methods included training, mentoring, and direct implementation, such as creating social media accounts for promotion, adopting WhatsApp Business for customer communication, and using Google Forms for online booking. The results show that the partner is now able to manage social media effectively, respond to customers more quickly, and streamline the booking process through digital forms. This initiative positively impacted business visibility, customer satisfaction, and operational efficiency, demonstrating that simple digital technologies can effectively support the sustainability and competitiveness of tourism-related MSMEs.